2008
DOI: 10.1369/jhc.2008.952788
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Epithelial Cells and Their Relationship to Immunocompetent Cells in Rat Molars: A Confocal and Transmission Electron Microscope Study

Abstract: This study sought to investigate the distribution of cytokeratin (CK)-immunopositive cells and their relationship to immunocompetent ED1- and OX6-immunopositive cells in rat periodontium by immunohistochemistry and electron microscopy. CK-immunopositive cells were generally distributed along the surface of the tooth root. They could also be found between root dentin and cementum, in the perivascular space, and close to or in the alveolar bone lacunae. ED1-immunopositive cells exhibited a compact shape with sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 30 publications
4
7
0
Order By: Relevance
“…In the present study, blood vessels were sometimes observed close to the ME cells. Similar findings have been reported in previous studies [18,24]. In such areas, immunocompetent cells are close to or in contact with the ME cells [18].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In the present study, blood vessels were sometimes observed close to the ME cells. Similar findings have been reported in previous studies [18,24]. In such areas, immunocompetent cells are close to or in contact with the ME cells [18].…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings have been reported in previous studies [18,24]. In such areas, immunocompetent cells are close to or in contact with the ME cells [18]. However, the present study did not focus on the relationship between them.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations